Pengembangan LMS Berbasis Google Sites untuk Meningkatkan Minat Belajar Siswa pada Materi Alat Optik di SMAS Istiqlal Delitua - Riska Hayani; Sutri Novika; Jafri Haryadi; Lia Afriyanti Nasution (FKIP Universitas Khairun, 2025)
This study aims to evaluate the validity, practicality, and effectiveness of Learning Management System (LMS) media developed using Google Sites for teaching Optical Instrument material to Class XI students at SMAS Istiqlal Delitua. The study focuses on the development of an LMS to enhance students' learning interest. The subjects of this research were 29 students from Class XI IPA 1. The research adopted the ADDIE model for development. The results revealed that the LMS is highly feasible as a learning medium. Assessments by material and media experts yielded average feasibility scores of 93.3% and 91.2%, respectively, both categorized as